Association of albumin to non-high-density lipoprotein cholesterol ratio with mortality in peritoneal dialysis patients - Yongjie Xie; Xiaoran Feng; Youqun Gao; Xiaojiang Zhan; Fenfen Peng; Qian Zhou; Xianfeng Wu; Xiaoyang Wang; Na Tian; Qingdong Xu; Ning Su; Xingming Tang; et al. (Renal Failure)
Objective Malnutrition and inflammation are associated with mortality in peritoneal dialysis (PD) patients. Serum albumin and non-high-density lipoprotein cholesterol (non-HDL-C) are independently associated with mortality in PD patients. Combining albumin and non-HDL-C with mortality may be more plausible in clinical practice.Methods This retrospective cohort study included 1954 Chinese PD patients from 1 January 2009 to 31 December 2016. Kaplan–Meier curve was used to determine the relationship between albumin to non-HDL-C ratio and all-cause mortality. Cox regression analysis was applied to assess the independent predictive value while adjusting for confounding factors. Competitive risk analysis was used to examine the effects of other outcomes on all-cause mortality prognosis.Results In the 33-month follow-up period, there were 538 all-cause deaths. Kaplan–Meier analysis presented significant differences in all-cause mortality. Multivariate Cox regression showed that the risk of all-cause mortality was lower in the moderate group (9.36–12.79) (HR, 0.731; 95% CI, 0.593–0.902, p = 0.004) and the highest group (>12.79) (HR, 0.705; 95% CI, 0.565–0.879, p = 0.002) compared to the lowest group (≤9.36). Competitive risk analysis revealed significant differences for all-cause mortality (p < 0.001), while there was no statistical significance for other competing events.Conclusions Low albumin to non-HDL-C ratio was associated with a high risk of all-cause mortality in PD patients. It may serve as a potential prognostic biomarker in PD patients.